Direct Election System In City of Makassar In Islamic Law Perspective - Akil Tahir; Lamba Sultan; Darussalam Syamsuddin; Moh Sabri (Journal of Research and Multidisciplinary, 2019)
Direct Election System in Makassar City in Islamic Law Perspective, this is located in Makassar City, South Sulawesi Province. This type of research is descriptive qualitative. While the approach used in this study is a formal juridical approach. The results of the study indicate that the mechanism of direct elections in Makassar City in accordance with the 1945 Constitution, Article 18 paragraph (4) affirms: "Governors, Regents, and Mayors respectively as Heads of Provincial, Regency, and City Governments are democratically elected". It's just that there are still those that are not in line with the provisions of Islamic law and law, for example being elected as Regional Head because of nepotism, using the power of money or called money politics. Regional Head in Makassar City, it can be said that he is competent. However, when viewed from the post-conflict local election law, it turns out that there is one important requirement that is omitted, namely about public testing, so that it is not chosen from its capacity, but is chosen more in terms of the strength of political parties and in terms of the strength of the funds. The character of the voters is also diverse and generally, there are still some whose voting rights can be bought with money.